Exploring the potential of Laportea decumana extract compounds as COX-1 and COX-2 inhibitors: An in silico study - Simaremare, Eva S.; Kurniawan, Fransiska; Hartati, Rika; Tjahjono, Daryono H. (Narra J, 2025)
Laportea decumana (Roxb.) Wedd., known as itchy leaves, is traditionally used for pain relief due to its bioactive compounds. However, previous studies were limited by resource-intensive in vivo methods and a lack of mechanistic insights into cyclooxygenase (COX)-1 and COX-2 binding. The aim of this study was to identify compounds in the n-hexane and ethyl acetate extracts of L. decumana with potential as COX-1 and COX-2 inhibitors and to predict their binding affinity and stability within the binding pocket through molecular dynamics simulations. Leaves collected from Arso, Keerom Regency, Papua, Indonesia, were dried, sieved into simplicia, and macerated with n-hexane to obtain a n-hexane extract. The residual simplicia was further macerated with ethyl acetate to produce an ethyl acetate extract. N-hexane extract compounds were analyzed by gas chromatography-mass spectrometry (GC-MS), and ethyl acetate extract compounds by liquid chromatography-mass spectrometry (LC-MS). Identified chemicals were used in in silico evaluations targeting COX-1 and COX-2. This study identified ten compounds with high performance in docking analysis, which were further evaluated by molecular dynamics. The n-hexane extract contained 31 compounds, while the ethyl acetate extract contained 27. Among these, 4,8,12,16-tetramethylheptadecan-4-olide from the n-hexane extract demonstrated the strongest affinity for both COX-1 and COX-2, with binding free energies of -41.62±1.03 kcal/mol and -33.05±0.11 kcal/mol, respectively. Its interactions were comparable to those of native ligands, with superior binding free energy. In the ethyl acetate extract, pseudosantonim demonstrated the highest affinity for COX-1 (-24.41±1.32 kcal/mol), while arteamisinine showed strong potential as a COX-2 inhibitor (-23.53±0.30 kcal/mol). In conclusion, 4,8,12,16-tetramethylheptadecan-4-olide was the most potent COX-1 and COX-2 inhibitor, pseudosantonim was the most effective COX-1 inhibitor, and arteamisinine demonstrated COX-2 inhibitory potential. Further validation through in vitro or in vivo studies is recommended.